Effect of calf sex on some productive, reproductive and health traits in Holstein cows - Chegini, Arash; Ghavi Hossein-Zadeh, Navid; Hosseini-Moghadam, Hossein (Spanish Journal of Agricultural Research, 2015)
Records of Holstein cows from March 1992 to April 2008 from 194 large herds and comprising from 402,716 records for productive traits to 178,344 records of somatic cell count were used to study the effect of calf sex in different parities and calving season on the subsequent productive, reproductive and health traits in Holstein cows. T-test procedure of SAS software was used to investigate the effect of calf sex and season of calving on aforementioned traits. Cows with female calves had higher milk and fat yield, persistency of milk and fat yield and longer lactation length, while cows that gave birth to male calves had shorter calving interval and longer productive life. Also, cows with female calves had higher milk yield per day of lactation in the first two parities, but there was no difference in milk yield per day of lactation for parities ≥ 3. There was no relationship among mean somatic cell count and sex of born calf. Fall calves had the highest adjusted milk yield and milk yield per day of lactation, however, winter calves had the longest lactation lengthand productive life and the highest somatic cell count. Results from this study demonstrate that it seems necessary to consider the effect of calf sex on aforementioned traits when making decision to use sexed semen or conventional semen.